ENHANCING STUDENT COMPETITIVENESS THROUGH PROFESSIONAL CERTIFICATION: A CASE STUDY AT STIE GANESHA - tuti herawati (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study addresses the critical gap between academic preparation and industry requirements by examining the implementation of competency assessment and professional certification at STIE Ganesha. The research aims to analyze how these systems enhance graduate competitiveness within the ASEAN Economic Community framework. Using a qualitative descriptive approach, the study engaged 100 students and 10 assessors through in-depth interviews, participatory observation, and documentation analysis of managerial competency schemes. Empirical results demonstrate that 91.3% of participants showed significant improvement in self-confidence post-certification, while 78.2% reported substantial career advancement. The certification program effectively equips graduates with both academic credentials and BNSP-certified competency recognition. These findings imply that higher education institutions should strengthen industry-aligned certification programs and develop strategic partnerships with professional bodies. The study provides practical insights for optimizing certification frameworks to bridge the academia-industry divide and enhance graduate employability in competitive job markets